PENINGKATAN PERKEMBANGAN MOTORIK HALUS PADA ANAK USIA 5-6 TAHUN DI PAUD TERPADU CERIA - Sri Hayati; Fadilah Fadilah; Lukmanulhakim Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis research is motivated by the still low fine motor development in children. The problem in this study is "How is learning about weaving activities to improve fine motor development in children aged 5-6 years in PAUD Integrated Cheerful?". The form of this research is classroom action research with descriptive methods. Research subjects were 1 teacher and 20 children. Based on the results of research that has been done and through the results obtained after data analysis, in general it can be concluded that: 1) Planning of weaving learning in children aged 5-6 years. 2) The implementation of learning to weave with the steps taken by the teacher based on plans that have been made which include environmental footing, footing before playing, footing when playing and footing after playing. 3) Increasing fine motor skills of children aged 5-6 years by: a) Coordinating with various media and paper weaving activities reaching 80%. b) Mimic the shape of the plait by using fingers to weave in the correct position. In this case the child is able to weave by himself with fast and neat activities reaching 80%.Keywords: Fine motor, Children 5-6 years old